Beyond Atherothrombotic Disease in Acute Coronary Syndrome - Mora,Mayra Alejandra (2021)
Abstract Half of the global population over 20 years of age will be affected by cardiovascular disease. Cardiovascular events in young people is challenging. Spontaneous coronary artery dissection is a non-traumatic and non-iatrogenic separation of the coronary arterial wall and is an uncommon and underdiagnosed cause of acute myocardial infarction predominately found in young women. Medical management has been more widely accepted, with percutaneous and surgery treatment reserved for precise indications. Optimal control of individual risk factors is essential in order to avoid recurrences.